Effectiveness of Managerial Ownership in Moderating the Impact of Green Accounting and Green Intellectual Capital on Financial Performance - Sri Nuraini Rahmawati (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to obtain empirical evidence regarding the effect of green accounting and green intellectual capital on financial performance with managerial ownership as a moderating variable. Design/methodology/approach – This research uses quantitative research. The sample in this study were industrials sector companies listed on the Indonesia Stock Exchange in 2021-2024, totaling 41 companies. The analysis technique used to test the hypothesis is multiple regression analysis and moderation interaction regression using EViews 9 software. Findings – The results of this study indicate that green accounting has a negative and statistically insignificant effect on financial performance. In contrast, green intellectual capital has a positive and statistically significant effect on financial performance, and managerial ownership has a positive and statistically significant effect on financial performance. However, managerial ownership does not strengthen the effect of green accounting on financial performance, while managerial ownership strengthens the effect of green intellectual capital on financial performance. Research limitations/implications – This study discusses corporate financial performance as well as other factors such as green accounting, green intellectual capital, and managerial ownership, focusing on industrials sector companies. This study makes a novel contribution by placing managerial ownership as a moderating variable that strengthens the relationship to explain variations in corporate financial performance amidst increasing demands for sustainable business practices. Originality/value – This study is a new contribution to Indonesian literature because it integrates green accounting, green intellectual capital, and managerial ownership into a single research framework. The evidence produced can be used as a reference for academics, practitioners, and regulators to understand the role of managerial ownership in strengthening sustainability practices that impact corporate financial performance.